What are the sensitivity and specificity of serum immunoassay testing in adults with allergic rhinitis?. Issue 9 (September 2016) - Groetsch, Stefan; Keleher, Eamon C.
Abstract : Evidence‐Based Answer : Radioallergosorbent testing (RAST) of total serum IgE has poor sensitivity for allergic rhinitis; however, the sensitivity of RAST ranges from 64% to 98% and the specificity ranges from 90% to 100% for specific nasal allergens. The newer CAP‐RAST is even more accurate (SOR: B, diagnostic cohort studies).